Locoregional and distant recurrence for HPV-associated oropharyngeal cancer using AJCC 8 staging. (December 2020) - Contrera, Kevin J.; Smile, Timothy D.; Mahomva, Chengetai; Wei, Wei; Adelstein, David J.; Broughman, James R.; Burkey, Brian B; Geiger, Jessica L.; Joshi, Nikhil P.; Ku, Jamie A.; Lamarre, Eric D.; Lorenz, Robert R.; et al.
Highlights: HPV-associated oropharyngeal cancer has unique patterns of recurrence. Risk of locoregional recurrence is stratified by smoking, T/N category, and stage. Risk of distant recurrence is only stratified by smoking and not by stage. Abstract: Introduction: The objective of this study is to evaluate locoregional and distant failure for human papillomavirus-associated (HPV+) oropharyngeal squamous cell carcinoma (OPSCC) using American Joint Committee on Cancer eighth edition (AJCC 8) staging. Materials and methods: Retrospective cohort study of 457 patients with HPV + OPSCC, treated with platinum-based chemoradiation from 2002 to 2018, followed for a median of 4.3 years. Time to locoregional failure (TTLRF) and distant failure (TTDF) were estimated by Kaplan-Meier method. Log-rank, recursive partitioning analysis (RPA), and multivariable Cox proportional hazards were used to evaluate associated factors and stratify risk. Results: Rates of five-year locoregional control (LRC) and distant control (DC) were 92% (95% CI, 90–95%) and 89% (95% CI, 85–92%), respectively. Smoking, T4, N3, and stage III were associated with significantly worse TTLRF. RPA identified three distinct locoregional failure groups: cT1-3 and <19 pack-years vs. cT1-3 with ≥19 pack-years vs. cT4 (five-year LRC: 97% vs. 90% vs. 82%, P <  .0001). The only factor associated with significantly worse TTDF was smoking status, while stage was not correlated. RPA identified two prognostic groups: former or never smokers vs. current smokers (five-year DC: 92% vs. 77%, P  = .0003). Discussion: In the largest evaluation of HPV + OPSCC after platinum-based chemoradiation using AJCC 8, risk for locoregional recurrence was stratified by smoking, T category, N category, and overall stage. Risk of distant recurrence was only stratified by smoking status and not related to stage. This has implications for surveillance and clinical trial design.